Implikasi Penggunaan Platform Media Sosial dalam Pendidikan Agama - Rizkiyah, Selly; Rizqin, Indira Zein; Baktiar Putri, Milla Akbarany (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2024)
Abstract Nowadays, the era is growing and there is development not only in terms of socio-economics but also in the field of education, Islamic education is also growing rapidly. the utilization of technology as a learning medium for Islamic religious education can make learning more interesting for Gen Z in a increasingly digital era and make the acquisition of knowledge not monotonous. This research utilizes social media as an educational medium in the digital era. this research uses qualitative and quantitative research methods. Social media is main theme and the impact of using social media platforms on religious education is discussed. The information is collected using qualitative and quantitative methods. The study states that the use of social media with its diverse capabilities can serve as an educational tool in the digital era. However, the use of social media does not only provide positive impact but also negative impacts. Therefore, generation Z is expected to follow the training provided so that it can run effectively